Outcomes of VAC versus conventional dressings in patients with lower limb ulcer - Janugade, Hemant B.; Chabbra, Raunaq S.; Das, Ankur G.; Surushe, Aniket; Saygaonkar, Harshvardhan (International Surgery Journal, 2018)
Background: Chronic leg ulcers are a significant cause of morbidity in developing countries causing a significant burden on the health care system. The orthodox methods of dressing the wound requires long duration of hospital stay. The recent technique of vacuum assisted closure (VAC) has brought about new horizons in wound management with better outcomes. Methods: A comparative randomized case control study was conducted with a total of 60 patients from November 2015 to December 2017 in patients admitted with lower limb ulcers to KIMSDU, Karad, Maharashtra. Results: The mean graft uptake of Group A(VAC) and Group B (conventional dressings) was 82.23±15.60 and 70.07±18.42 respectively. Healing was achieved in minimum of 11 days and maximum of 48 days in Group A and minimum of 22 days and maximum of 59 days in Group B. The mean duration of wound healing in Group A and Group B was 27.70±9.57 and 41.93±11.58 days respectively. The duration of hospital stay was minimum of 13 days and maximum of 50 days in Group A and minimum of 24 days and maximum of 60 days in Group B. Conclusions: Rate of granulation tissue formation, overall graft survival and patient compliance was better in vacuum assisted closure dressing group as compared to conventional dressing group. It was also seen that the overall hospital stay and post-operative complications were less in the vacuum assisted closure dressing group.